Modern and comprehensive soil studies in grape agrocenoses in Azerbaijan - Ikhtiar, Anara Nasirova (International Journal of Advances in Applied Sciences, 2024)
The article presents some results of a comparative analysis of the agrochemical, microbiological, and environmental properties of grape plants and soil types common in regions located on the slopes of the Lesser Caucasus. The objectives of this study were to assess the current state and quality of soils used for vineyards in some villages of the Ganja-Kazakh economic region, taking into account the long-term use of fertilizers and chemicals to protect plantations from various diseases for the resulting wine materials. Growing and exporting grapes is of great importance for the development of the economy of the Republic of Azerbaijan. Since it is a break-even plant, expanding the area under grapes to attract wetlands to agriculture has been an important issue for soil scientists in recent years. During the period of rapid development of viticulture in the republic, ensuring rapid harvesting and longevity of vineyards is one of the important scientific and practical tasks.